Analysis of The Effort of The Local Government in Improving Education in Hasang Village - Khoirul Fadli Fadli; Fadli Azmi; Nur Rizky Arini Lubis; Novia Armaya Sipahutar; Halimatussa' Diyah Br Tanjung; Aulia Hakim; Sri Wahyuni (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2022)
Education is the foundation of hope for improving the quality of human resources. Children are the main priority in education, because they will be the successors of the nation and religion. Education is a human right as well as a means to realize other human rights. As an enabling right, education is the main target through which adults and especially children who are economically and socially marginalized can lift themselves out of poverty and find ways to be involved in their communities, because education plays an important role in empowering women, protecting children from hazardous work and sexual exploitation. The encouragement factor from family, environment, and teachers is very influential in the spirit of taking education in Hasang Village. In Hasang Village, there are some parents who still lack awareness of the importance of education, plus the damaged road access in this village reduces the enthusiasm of the residents in taking education to a higher level. The purpose of this study is to analyze the local government's efforts to improve education in Hasang Village. This research is descriptive using survey and observation methods. So it can be concluded that the government.